2010
DOI: 10.1111/j.1365-263x.2010.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary dental anomalies in children with cleft lip and palate: a controlled study

Abstract: In both UCLP and BCLP subjects the most prevalent missing teeth were the lateral incisors. The dental anomalies occurred predominantly in the cleft area, thus suggesting that the effect of the cleft disturbance is more local than general on the dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 20 publications
11
70
0
20
Order By: Relevance
“…The knowledge of developmental dental disorders in cleft lip and palate children can provide valuable information for treatment planning at an early age [6][7] . A recent study concluded that operated unilateral complete cleft lip and palate children showed serious craniofacial deformities and the craniofacial growth was influenced especially in maxilla 8 , but no true consensus has been reached at this time about the influence of surgery on facial growth.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of developmental dental disorders in cleft lip and palate children can provide valuable information for treatment planning at an early age [6][7] . A recent study concluded that operated unilateral complete cleft lip and palate children showed serious craniofacial deformities and the craniofacial growth was influenced especially in maxilla 8 , but no true consensus has been reached at this time about the influence of surgery on facial growth.…”
Section: Introductionmentioning
confidence: 99%
“…Other abnormalities are also frequently reported: microdontia 11 or a double lateral incisor 16 . There may also be agenesis of the second premolars, structural abnormalities (enamel hypoplasia) 3 and delayed root construction 7 .…”
Section: Unilateral Cleft Lip and Palatementioning
confidence: 99%
“…In fact 40 % of CLP patients are missing maxillary lateral incisors, usually on the side of the cleft 1,7,14 . So when orthodontists are establishing their treatment plans for these children they should make a careful assessment of residual spaces in the dental arch to determine if the child has missing or doubled maxillary lateral incisors.…”
Section: -Orthodonticsmentioning
confidence: 99%